Effect of Fusaric Acid (FA) Bio-stress on Certain Morphological Parameters for Potato (Solanum tuberosum. L) Cultivars in Vitro - Altinawi , E. A.; Albiski , F.; Faddoul , J. (Iraqi Journal of Science, 2023)
The experiment was carried out with the aim of studying the effect of biological stress on some morphological parameters of ten varieties of potatoes grown in vitro. Biological stress was applied by adding different concentrations of fusaric acid (0, 0.0125, 0.025, 0.05, 0.1, 0.2 mM), to the growth medium MS, and some growth parameters were measured, such as plant height (cm), number of leaves (leaf/plant¹), leaf area (mm²), number of roots (root.plant¹) and length it (cm), wet and dry weight of the plant (g). The results showed that the studied varieties were different in the response to biological stress according to the studied parameters. The addition of fusaric acid led to reduce all growth parameters compared with the control. The cluster analysis showed that based on the sum of the relative values ​​of the studied growth parameters, the studied varieties were distributed in three different groups: The first group includes three tolerant varieties to biological stress, and these are Toronto, Barcelona, and Suria). The second group includes four Moderate varieties of bio-stress, and these are Fabulla, Nectare, Spunta, and Ardappel. The third group included the following sensitive varieties, 7-four-7, Farida, and Joly. The results indicate that the in vitro screening technology can be used as a fast and efficient method to investigate the genetic variation of biological stress tolerance in potatoes.